1998
DOI: 10.1542/peds.101.6.963
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cardiac Surgery: The Effect of Hospital and Surgeon Volume on In-hospital Mortality

Abstract: Both hospital volume and surgeon volume are significantly associated with in-hospital mortality, and these differences persist for both high-complexity and low-complexity pediatric cardiac procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
158
3
6

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(177 citation statements)
references
References 8 publications
10
158
3
6
Order By: Relevance
“…This is in common with another study with the same characteristics, 19 where no significant difference were observed between the two groups assessed, and also with other work in the area in terms of the age groups most affected. 19,20 The distribution of type of heart disease in the current study was also similar to what is found in the literature, where left-right shunt heart diseases are the most common as the most common CHD. 19,20 Also of note is group 5 (22.8%), complex heart disease, a pattern that is common at referral centers for pediatric heart surgery, as is the case at the study center.…”
Section: Discussionsupporting
confidence: 88%
“…This is in common with another study with the same characteristics, 19 where no significant difference were observed between the two groups assessed, and also with other work in the area in terms of the age groups most affected. 19,20 The distribution of type of heart disease in the current study was also similar to what is found in the literature, where left-right shunt heart diseases are the most common as the most common CHD. 19,20 Also of note is group 5 (22.8%), complex heart disease, a pattern that is common at referral centers for pediatric heart surgery, as is the case at the study center.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have shown that, in the past two decades, the hospital and surgeon volume are closely associated with better surgical outcome with lower postoperative complications or mortalities, such as paediatric cardiac surgery, 4 repair of abdominal aortic aneurysm, 5 coronary artery bypass graft surgery, 6 ventriculo-peritoneal shunt procedures, 7 total hip replacement surgery, 8 and colon cancer surgery. 9 However, only few studies reported the relationship between provider volume and the incidence of postoperative endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%
“…40 The relation of in-hospital mortality rates to case volume for congenital heart surgery has been examined in studies using statewide administrative data. [41][42][43][44] All have shown a significant correlation between improvement in severity-adjusted mortality rate and increasing institutional case volume. However, institutional case volume explains only a relatively small fraction of the variability in outcomes among pediatric heart surgery programs, and uncommon outcomes such as mortality are difficult to measure with statistical precision for smaller programs.…”
Section: Quality Of Carementioning
confidence: 99%